2017
DOI: 10.1097/ta.0000000000001474
|View full text |Cite
|
Sign up to set email alerts
|

The effect of blood transfusion on compensatory reserve

Abstract: Care management, level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 43 publications
4
33
1
Order By: Relevance
“…We applied the Generalized Estimating Equation method (GEE) to produce a Receiver Operating Characteristic (ROC) area under the curve (AUC) for the point of decompensation of 0.8910, as shown in Figure 6. This ROCAUC produced by the 1D CNN of the present study compares favorably with ROCAUCs generated from a previous machine-learning [14], [15], 0.79-0.83 for bleeding trauma patients [16], [17], [18], and 0.81-0.90 in humans with controlled blood loss [19], [20], [21]. This metric focuses only the CRM algorithm performance at the single point of decompensation, while the mean squared error (MSE) computed over the entire experiment is indicative of algorithm performance during a progressive hypovolemic episode.…”
Section: Resultssupporting
confidence: 58%
“…We applied the Generalized Estimating Equation method (GEE) to produce a Receiver Operating Characteristic (ROC) area under the curve (AUC) for the point of decompensation of 0.8910, as shown in Figure 6. This ROCAUC produced by the 1D CNN of the present study compares favorably with ROCAUCs generated from a previous machine-learning [14], [15], 0.79-0.83 for bleeding trauma patients [16], [17], [18], and 0.81-0.90 in humans with controlled blood loss [19], [20], [21]. This metric focuses only the CRM algorithm performance at the single point of decompensation, while the mean squared error (MSE) computed over the entire experiment is indicative of algorithm performance during a progressive hypovolemic episode.…”
Section: Resultssupporting
confidence: 58%
“…The CRM, designed to measure physiologic reserve, was the only parameter to demonstrate a difference between the groups. Previous reports also support the capability of CRM measurements to detect low volumes of blood loss . Despite the decline in CRM values throughout the testing day, the CRM nadir, reached at the end of the testing day, was 0.69 ± 0.24, well above the manufacturer's cutoff for moderate compromise .…”
Section: Discussionsupporting
confidence: 56%
“…In one study, CRM was found to be significantly lower (0.17) in patients with severe hemorrhage due to penetrating trauma resulting in relative anemia (as indicated by lower hematocrit and hemoglobin) compared with a CRM of 0.56 in patients with blunt trauma who were not actively bleeding . When patients with gastrointestinal bleeding required red blood cell transfusion, a nearly 11% increase in CRM was associated with a 22% increase in hemoglobin . CRM has consistently shown accuracy in assessing fluid interventions when applied during resuscitative treatment of hemorrhage in patients suffering from Dengue hemorrhagic fever, blunt or penetrating trauma with significant blood loss, internal bleeding, and sepsis or septic shock .…”
Section: Evidence For Crm Use In Clinical Settingsmentioning
confidence: 99%